Platelet indices in acute coronary syndrome patients - Shahin Keshtkar Rajabi; Faeze Delpasand; Soroush Nematollahi; Mohammad Soleimani; Ehsan Rikhtegar; Mohammad Amin Abbasi (Journal of Research in Applied and Basic Medical Sciences, 2023)
Background & Aims: platelets play crucial role in acute coronary syndromes (ACS). The importance of platelets in the development and spread of acute coronary syndromes (ACS) is well known. Most studies tried to find an association between platelet indices and cardiovascular diseases (CVD) risk factors; however, the results contradict, and despite the relative ease of obtaining the platelet indices, their use in clinical practice is still limited. This study aimed to investigate the relationship between platelet indices and other influencing factors including age, gender, underlying diseases, and fat profile in determining the risk of ACS. Materials & Methods: From September 2019 to March 2020, a consecutive of 101 patients (76 men and 25 women) admitted to the CCU in firoozabadi hospital, Tehran, Iran, were enrolled in this cross-sectional study. Patients who had a history of platelet disorders, myeloproliferative disorders, thyroid dysfunctions, receiving blood products, cancers and chemotherapy, and patients who had missing Mean platelet volume (MPV) in current or prior admissions were excluded from the study. Patients were divided into the MI and the UA (Unstable Angina) groups. Data were presented as means ± SD and qualitative variables as frequency (percentage) were considered. Statistical analyzes were performed with SPSS software version 20. Results: The mean age of patients was 62.5 ± 13.16 years. Age, gender, underlying disease, troponin, ejection fraction, HDL, LDL, cholesterol, and triglyceride were assessed in the patients. The mean fasting blood sugar and LDL were significantly different between the two groups of MI and Unstable Angina (UA), in which P-values were 0.001 and 0.02, respectively. Comparing platelet indices, including platelet count, PDW, and MPV in the two groups, indicated a difference in the PDW variable (P-value 0.008). Conclusion: Platelet count did not show any significant changes or relation with MI and UA patients. MPV was not significantly higher in the MI group than the UA group, but higher MPV values were related to a higher mortality rate. Elevated PDW was significantly correlated with both MI groups and mortality, thus can be used as a prognostic factor.